Genome-wide association analysis in primary sclerosing cholangitis identifies two non-HLA susceptibility loci - Melum, Espen; Franke, Andre; Schramm, Christoph; Weismüller, Tobias J.; Gotthardt, Daniel; Offner, Felix A.; Juran, Brian D.; Laerdahl, Jon K.; Labi, Verena; Björnsson, Einar; Weersma, Rinse K.; Henckaerts, Liesbet; et al. (Nature genetics, 2011)
Tom Karlsen and colleagues report a genome-wide association study for primary sclerosing cholangitis, a chronic bile duct disease. They identify susceptibility loci at MST1 and near BCL2L11.